Answer:
P = 30 degrees, PQ = 6.93, PN = 8
Step-by-step explanation:
For the angle, just subtract the angles you already know from 180, so 180 - 90 - 60= P. P = 30 degrees.
For PQ, use tan60 = x/4, or 4tan(60), which equals 6.93.
For PN, use cos60 = 4/x, or 4/cos60, which equals 8.
Hopefully this helps- let me know if you have any questions!
For the first part:Every shirt she grabs, will cost her dollars, so if she grabs 3 shirts, then the cost of the shirts is:
![12+12+12=3(12)](https://tex.z-dn.net/?f=12%2B12%2B12%3D3%2812%29)
With the same rationale, if she grabs 2 pairs of jeans, the cost of the jeans is:
![19+19=2(19)](https://tex.z-dn.net/?f=19%2B19%3D2%2819%29)
So, her total is:
![3(12)+2(19)](https://tex.z-dn.net/?f=3%2812%29%2B2%2819%29)
If you subtract 3 from the total, then the expression is:
For the second part:If she's paying 3 less for each shirt, then the cost of 3 shirts will become:
![(12-3)+(12-3)+(12-3)=3(12-3)](https://tex.z-dn.net/?f=%2812-3%29%2B%2812-3%29%2B%2812-3%29%3D3%2812-3%29)
In the same fashion, for the two jeans:
![(19-3)+(19-3)=2(19-3)](https://tex.z-dn.net/?f=%2819-3%29%2B%2819-3%29%3D2%2819-3%29)
So the expression for the total cost is:
For number three:The amounts are different because the cost of the total purchase is different than the cost of each element that makes up the total purchase.
For number four:If you're the owner, you want to give the smallest amount of discount (the one in part 1/a).
So you could clarify by saying there's 3 dollars of the TOTAL purchase's cost.
Answer:
x < -17
Step-by-step explanation:
-3-7x - 41 - 7>68
Combine like terms
-7x-51>68
Add 51 to each side
-7x-51+51>68+51
-7x > 119
Divide each side by -7, remembering to flip the inequality
-7x/-7 < 119/-7
x < -17
Answer:
The line equation is given as: 3 y = 2 x - 9
Step-by-step explanation:
Here, Y intercept is at point ( 0.-3)
So, at x = 0, y = -3
or, C = -3
Also, the point on the equation line is (x,y) = (-9,-9)
Now, by <u>SLOPE INTERCEPT FORM</u> of a line equation,we get:
y = m x + C : m = slope of line ......... (1)
So, substituting the values of C and (x,y) , we get:
-9 = m (-9) + (-3)
or, -9 + 3 = - 9 m
or, m = -6/-9 = 2/3
or, m = 2/3
Now, substitute the value of m back in to the line equation (1)
![y = m x + C \implies y = (\frac{2}{3}) x - 3\\\implies 3y = 2x - 9](https://tex.z-dn.net/?f=y%20%3D%20m%20x%20%2B%20C%20%20%20%5Cimplies%20%20y%20%3D%20%28%5Cfrac%7B2%7D%7B3%7D%29%20x%20-%203%5C%5C%5Cimplies%203y%20%3D%202x%20-%209)
Hence, the line equation is given as: 3 y = 2 x - 9.
The two numbers are 8 and 12.
When added, you get a sum of 20.
When multiplied, you get a product of 96.